2010
DOI: 10.3791/2413
|View full text |Cite
|
Sign up to set email alerts
|

Micropatterned Surfaces to Study Hyaluronic Acid Interactions with Cancer Cells

Abstract: Cancer invasion and progression involves a motile cell phenotype, which is under complex regulation by growth factors/cytokines and extracellular matrix (ECM) components within the tumor microenvironment. Hyaluronic acid (HA) is one stromal ECM component that is known to facilitate tumor progression by enhancing invasion, growth, and angiogenesis 1 . Interaction of HA with its cell surface receptor CD44 induces signaling events that promote tumor cell growth, survival, and migration, thereby increasing metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…matrix stiffness) and composition of the ECM, features which are reported to be abnormal in the tumor environment [90], direct cell behavior. In our lab, we have utilized this technique to address vascular network assembly from endothelial progenitor cells on micropatterned fibronectin and fibrin gel strips [91] and the adhesion of different breast cancer cell lines on micropatterned hyaluronan [92], discovering that substrate geometry and topography impact cellular responses. This approach also allows the investigation of single-cell interactions between ECs and cancer cells at different stages of tumorigenesis [92].…”
Section: Future Outlook: Engineering-centered Approaches For Investigmentioning
confidence: 99%
See 1 more Smart Citation
“…matrix stiffness) and composition of the ECM, features which are reported to be abnormal in the tumor environment [90], direct cell behavior. In our lab, we have utilized this technique to address vascular network assembly from endothelial progenitor cells on micropatterned fibronectin and fibrin gel strips [91] and the adhesion of different breast cancer cell lines on micropatterned hyaluronan [92], discovering that substrate geometry and topography impact cellular responses. This approach also allows the investigation of single-cell interactions between ECs and cancer cells at different stages of tumorigenesis [92].…”
Section: Future Outlook: Engineering-centered Approaches For Investigmentioning
confidence: 99%
“…In our lab, we have utilized this technique to address vascular network assembly from endothelial progenitor cells on micropatterned fibronectin and fibrin gel strips [91] and the adhesion of different breast cancer cell lines on micropatterned hyaluronan [92], discovering that substrate geometry and topography impact cellular responses. This approach also allows the investigation of single-cell interactions between ECs and cancer cells at different stages of tumorigenesis [92]. Others have utilized micropatterning to investigate the role of matrix geometry and stiffness on mammary epithelial cell transformation [93] and tumor spheroid generation [94].…”
Section: Future Outlook: Engineering-centered Approaches For Investigmentioning
confidence: 99%
“…We have reported that HMW-HA enhances EC barrier function (Singleton et al, 2006, 2010). The HA in the stroma of several cancers has been implicated in numerous processes including inhibition of apoptosis, stimulation of tumor cell proliferation, migration and invasion, epithelial mesenchymal transition, protection from immune cells, and regulation of intercellular space (Auvinen et al, 2013; Bollyky et al, 2009; Cho et al, 2012; Dickinson & Gerecht, 2010; Sironen et al, 2011; Tammi et al, 2008). Whether this stroma-associated HA also promotes resealing of new capillaries remains to be determined.…”
Section: Ha Regulation Of Endothelial Barrier Function During Tumomentioning
confidence: 99%
“…As a proof of principle, Chiu et al (38) micropatterned tumor cells and ECs together in spatially and geometrically defined regions of fibrinogen, methodology the authors believe will not only allow for studies of tumor cell-directed EC migration and capillary formation, but will permit patterning of numerous cell types on the same substrate. Work in our lab has demonstrated the specific adhesion of breast cancer cells on micropatterned HA surfaces (39) and endothelial progenitor cell elongation and unidirectional network assembly on micropatterned fibronectin and fibrin gel stripes (32), suggesting the role of spatial presentation of specific ECM molecules in regulating tumor and vascular cell behaviors. Overall, through control over the geometry and spacing of ECM molecules, investigators will be better equipped to address the complex interactions taking place between cancer and vascular cells during angiogenesis in the tumor environment.…”
Section: Engineering Approaches Using Ecm To Investigate Tumor Angiogmentioning
confidence: 99%